Effect of cyclophosphamide on tumorogenesis of the IL-6 and Hyper-IL-6 gene modified murine melanoma cells - Mackiewicz, Andrzej; Iżycki, Dariusz; Baksalary-Iżycka, Katarzyna; Gryska, Katarzyna; Łaciak, Maria; Nawrocki, Sergiusz (Contemporary Oncology/Współczesna Onkologia, 2004)
Background: The study was aimed at evaluating the effect of cyclophosphamide on the melanogenesis of the IL-6 and hyper-IL-6 gene modified murine melanoma cells. Animals and Experimental Design: Sixty-three (n=63), six-week-old C57/Bl6xC3H chimeric mice were injected with ”wild” type or with interleukin-6 (IL-6) or Hyper-6 (H6) gene modified B-78 murine melanoma cells and/or cyclophosphamide. Control groups were injected s.c. with ”wild” type (group I; n=7), IL-6 (group II; n=7), or H-6 (group III; n=7) gene modified B-78 murine melanoma cells (5x10 5 cells). In the experimental groups IA, IIA, and IIIA animals were intraperitoneally (i.p.) injected with cyclophosphamide (100 mg/kg) two days before inoculation of B-78 (group IA; n=7), B-78/IL-6 (group IIA; n=7) and B-78/H6 (group IIIA; n=7) melanoma cells (s.c.; 5x10 5 cells). In the experimental groups IB (n=7), IIB (n=7) and IIIB (n=7) combined treatment of B-78, B-78/IL-6 and B-78/H6 (respectively; s.c.; 5x10 5 cells) and cyclophosphamide (500 mg/kg; i.p., two days before inoculation of B-78 cells) was applied. We evaluated the kinetics of the tumor growth, mean survival time of the animals and immune response. The non-specific (NK cells) immunotoxicity as well as Th1/Th2 and Tc1/Tc2 shift were analyzed by flow cytometry. Results: The kinetics of the tumor growth study revealed significantly important inhibition of tumor growth in group III mice (day 35, <20 cm 3) treated with B-78/H6 mono-therapy. Application of combined B-78/IL-6 and B-78/H6 with cyclophosphamide (100 mg/kg; group IIIA) treatment resulted in significant extension of the survival and tumor growth inhibition. Flow cytometric analysis of the non-specific cytotoxicity showed no significant difference between control and experimental groups as well as in the Th1/Th2 and Tc1/Tc2 ratios. Conclusions: Application of low doses of cyclophosphamide resulted in inhibition of the potency of tumor to grow in vivo.